A new species of the sponge Raspailia (Raspaxilla) (Porifera: Demospongiae: Axinellida: Raspailiidae) from deep seamounts of the Western Pacific - Ekins, Merrick; Debitus, Cécile; Erpenbeck, Dirk; Hooper, John N.a. (Zootaxa, 2018)
A new species of Raspailia (Raspaxilla) frondosa sp. nov. is described from the deep seamounts of the Norfolk and New Caledonia Ridges. The morphology of the species resembles that of a frond or a fern, and its unique highly compressed axial skeleton of interlaced spongin fibres without spicules in combination with a radial extra axial skeleton of a perpendicular palisade of spicules, differentiate it from all other species of the subgenus. This species is compared morphologically to all 18 other valid species described in Raspailia (Raspaxilla).